The Court cases of the statement on the invalidation an arranged marriage with the calling assessors - SOKOŁOWSKI, JAROSŁAW (Prawo Kanoniczne, 2013)
In the teaching the level of all branch of knowledge demands today to arrive at the most appropriate decision, it is necessary referring to be expert that it to say assessor. After the label the terminology of the concept , assessor”, the main idea is firs of all focused on approaches of calling the assessor to take an active part in Canon Law, and especially in court case of the statement on the invalidation an arranged marriage. This study research has got the introduction and the conclusion. The introduction fills readers in problems of the issue, it contains the system of work and indicates to subject’s literature, and also to the basic source of lawsuit’s regulations such as John Paul the second’s Canon Low Code from 1983 and Instruction Dignitas connubii form 25.01.2005. The trial of this thesis does not use all issues connected with calling the assessors in lawsuit up. The interest is only about the manners of calling the assessor in Canon Law. It believes also, that in indirect approach raising the thesis issues can equally cause the subject of change of thinking the calling assessor, and especially it can find the answer to the current questions, who can be the calling assessor in Canon Law? The research’s result will introduce the readers in problems of the issue, which consists the system of logical and hard-headed work with support and indication of the subject’s literature. If somebody has the question about the subject’s literature, just the thing to underscore and trough of this issue there are the different monographic items, whether connected with this issue dip historical-law study.